Confiabilidade intra e inter avaliador do teste de 10 RM com resistência elástica na DPOC - Facio, Carina Araujo de (Universidade Federal de São Carlos, 2018)
Resistance training programs, especially concerning quadriceps muscle, have been indicated for patients with Chronic Obstructive Pulmonary Disease (COPD) to improve muscle strength. These patients present reduced muscle mass and strength, mainly in lower limbs, which is associated with worsening in functional capacity, quality of life and mortality prognosis. Resistance training may be performed with elastic resistances, which are less expensive, easily available, practical for use and have already been associated with improving in strength and muscle mass in patients with COPD. However, training load with elastic resistance is difficult to be determined, because of its properties. Submaximal tests, such as ten-repetitions maximum test (10RM), are better for elastic resistance. Even though 10 RM test with elastic bands has a qualitative evaluation with subjective concepts to determine load, it is not yet standardized. Moreover, it is not clear whether different raters are able to determine the training load by this test. This study aims to assess intra- and inter-rater reliability of the 10 RM test with elastic resistance for knee extension in subjects with stable COPD. This is a cross-sectional study, in which two blind raters performed 10 RM tests on two non-consecutive days, not exceeding seven-days interval. Thirty-two patients with stable COPD, men and women, over 50 years old were included. Patients underwent an incremental 10 RM test with Thera-Band® elastic bands on an adjustable ergonomic chair. Cohen weighted kappa coefficient and its 95% confidence interval (CI) was used for statistical analysis. The intra-rater agreement was κ = 0.63 (95% CI 0.43-0.83) in dominant lower limb (DLL) and κ = 0.63 (95% CI 0.41-0.85) in non-dominant lower limb (NDLL) for rater 1, while for rater 2 it was κ = 0.64 (95% CI 0.43-0.84) in DLL and κ = 0.58 (95% CI 0.36-0.81) in NDLL. The inter-rater agreement was κ = 0.74 (95% CI 0.580.90) for DLL and κ = 0.77 (95% CI 0.60-0.94) for NDLL in test 1. In test 2, values were κ = 0.81 (95% CI 0.68-0.94) for DLL and κ = 0.76 (CI 95% 0.60-0.93) for NDLL. In conclusion, there was moderate to good inter-rater reliability and good to very good inter-rater reliability in 10 RM test for knee extension with elastic bands in patients with COPD.
Intra and inter rater reability of 10 RM test with elastic resistance in COPD
Keywords: Fisioterapia; Doença Pulmonar Obstrutiva Crônica; Confiabilidade; Exercício físico; Resistência física; Elastic resistance; Reliability; Exercise; Chronic Obstructive Pulmonary Disease; Physical therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL